Reactive CEP: Integrating Complex Event Processing into Web Reactive Languages - Zimmerle, Carlos; Gama, Kiev (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2018: Proceedings of the 24th Brazilian Symposium on Multimedia and the Web, 2018)
The amount of data and events that Web applications deal with has increased largely in the recent years. This scenario tends to become even larger as new smart things are constantly being connected using Web technologies in the so-called Web of Things. Meanwhile, ways to react to those occurrences of events have been explored by distinct communities with different points of view. Two solutions have stood out, namely Complex Event Processing (CEP) and Reactive Languages (RLs). While both share similarities, RLs lack expressivity with regard to time and temporal operations. Furthermore, events play a major role in CEP, whereas RLs have time-changing values as their main abstraction. In this paper, we propose an integration of CEP and RLs by extending a functional reactive framework with CEP concepts and operations.